Unraveling acridine degradation mechanisms in PAH-contaminated soils using DNA-SIP combined with metagenomics and soil transcriptomics - Maria Jordán; Esteban Bustos-Caparros; Juan F. Gago; Zhenfa Zhang; Zhenyu Tian; David R. Singleton; Ramon Rossello-Mora; Magdalena Grifoll; Joaquim Vila (Journal of Hazardous Materials, 2026)

Bacterial benz(a)anthracene catabolic networks in contaminated soils and their modulation by other co-occurring HMW-PAHs - Sara N. Jiménez-Volkerink; Maria Jordán; David R. Singleton; Magdalena Grifoll; Joaquim Vila (Environmental Pollution, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genome-Wide Association Analysis of the Sense of Smell in U.S. Older Adults: Identification of Novel Risk Loci in African-Americans and European-Americans - Jing Dong; Annah Wyss; Jingyun Yang; T. Ryan Price; Aude Nicolas; Michael Nalls; Greg Tranah; Nora Franceschini; Zongli Xu; Claudia Schulte; Alvaro Alonso; Steven R. Cummings; et al. (Molecular Neurobiology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Early harvest of monsoon rice to address seasonal hunger in northwest Bangladesh - Florencia G. Palis; Arelene J. B. Malabayabas; Grant R. Singleton; Mohammed A. Mazid; David E. Johnson (Food Security, 2016)

Long-term simulation of in situ biostimulation of polycyclic aromatic hydrocarbon-contaminated soil - Stephen D. Richardson; Maiysha D. Jones; David R. Singleton; Michael D. Aitken (Biodegradation, 2012)

Pyrosequence analysis of bacterial communities in aerobic bioreactors treating polycyclic aromatic hydrocarbon-contaminated soil - David R. Singleton; Stephen D. Richardson; Michael D. Aitken (Biodegradation, 2011)

Stable‐isotope probing of the polycyclic aromatic hydrocarbon‐degrading bacterial guild in a contaminated soil - Maiysha D. Jones; Douglas W. Crandell; David R. Singleton; Michael D. Aitken (Environmental Microbiology, 2011)
Summary The bacteria responsible for the degradation of naphthalene, phenanthrene, pyrene, fluoranthene or benz[ a ]anthracene in a polycyclic aromatic hydrocarbon (PAH)‐contaminated soil were investigated by DNA‐based stable‐isotope probing (SIP). Clone libraries of 16S rRNA genes were generated from the 13 C‐enriched (‘heavy’) DNA recovered from each SIP experiment, and quantitative PCR primers targeting the 16S rRNA gene were developed to measure the abundances of many of the SIP‐identified sequences. Clone libraries from the SIP experiments with naphthalene, phenanthrene and fluoranthene primarily contained sequences related to bacteria previously associated with the degradation of those compounds. However, Pigmentiphaga ‐related sequences were newly associated with naphthalene and phenanthrene degradation, and sequences from a group of uncultivated γ‐ Proteobacteria known as Pyrene Group 2 were newly associated with fluoranthene and benz[ a ]anthracene degradation. Pyrene Group 2‐related sequences were the only sequences recovered from the clone library generated from SIP with pyrene, and they were 82% of the sequences recovered from the clone library generated from SIP with benz[ a ]anthracene. In time‐course experiments with each substrate in unlabelled form, the abundance of each of the measured groups increased in response to the corresponding substrate. These results provide a comprehensive description of the microbial ecology of a PAH‐contaminated soil as it relates to the biodegradation of PAHs from two to four rings, and they underscore that bacteria in Pyrene Group 2 are well‐suited for the degradation of four‐ring PAHs.

Effects of enrichment with phthalate on polycyclic aromatic hydrocarbon biodegradation in contaminated soil - David R. Singleton; Stephen D. Richardson; Michael D. Aitken (Biodegradation, 2008)

Identification and quantification of uncultivated Proteobacteria associated with pyrene degradation in a bioreactor treating PAH‐contaminated soil - David R. Singleton; Ramiah Sangaiah; Avram Gold; Louise M. Ball; Michael D. Aitken (Environmental Microbiology, 2006)
Summary Uncultivated bacteria associated with the degradation of pyrene in a bioreactor treating soil contaminated with polycyclic aromatic hydrocarbons (PAH) were identified by DNA‐based stable‐isotope probing (SIP) and quantified by real‐time quantitative PCR. Most of the 16S rRNA gene sequences recovered from 13 C‐enriched DNA fractions clustered phylogenetically within three separate groups of β‐ and γ‐Proteobacteria unassociated with described genera and were designated ‘Pyrene Groups 1, 2 and 3’. One recovered sequence was associated with the Sphingomonas genus. Pyrene Groups 1 and 3 were present in very low numbers in the bioreactor but represented 75% and 7%, respectively, of the sequences recovered from 16S rRNA gene clone libraries constructed from 13 C‐enriched DNA. In a parallel time‐course incubation with unlabelled pyrene, there was between a 2‐ and 4‐order‐of‐magnitude increase in the abundance of 16S rRNA genes from Pyrene groups 1 and 3 and from targeted Sphingomonas spp. over a 10 day incubation. Sequences from Pyrene Group 2 were 11% of the SIP clone libraries but accounted for 14% of the total bacterial 16S rRNA genes in the bioreactor community. However, the abundance of this group did not increase significantly in response to pyrene disappearance. These data indicate that the primary pyrene degraders in the bioreactor were uncultivated, low‐abundance β‐ and γ‐Proteobacteria not previously associated with pyrene degradation.

The effect of social organization on reproductive success and gene flow in colonies of wild house mice, Mus musculus - Grant R. Singleton; David A. Hay (Behavioral Ecology and Sociobiology, 1983)